Institutional Movement Logics and the Changing Shape of the US Social Movement Field, 1960–1995. (22nd January 2019) - Larson, Jeff; Lizardo, Omar
Abstract: In this paper, we develop an institutional movement logics approach to analyze the structure and dynamics of the US social movement field from 1960 to 1995. Using protest event data taken from the Dynamics of Collective Action dataset, we elicit the most salient combinations of issues, tactics, and targets reported to co-occur at protest events in four periods: 1960–1965, 1966–1972, 1973–1987, and 1988–1995. The analysis reveals the existence of six movement logics of varying breadth, flexibility, and stability. We also detect two important shifts in the overall structure of the field, one toward a broad and flexible form of state-centric politics and one toward several differentiated and narrowly defined forms of nonpolitical contention. We find support for two key premises of the institutional movement logics framework, limited diversity, and relative stability within and between logics while showing that a longer time frame offers a window on field dynamics not visible with shorter study time frames. We close by providing suggestions for further research seeking to build on the institutional movement logics approach.